The phonic footprint of marine tourism : exploring the underwater sound levels of whale watching and cruise vessels travelling within Skjálfandi Bay, Iceland - Bronte Mae Harris 1997- (2024)
Marine noise pollution is known to have detrimental impacts on marine species and ecosystems, and one of the dominant sources is vessel traffic, made worse by its rapid global expansion. These trends hold true for Icelandic waters as well, with boat-based tourism becoming especially prolific with growing popularity as a cruise destination and a renowned whale watching industry. In the town of Húsavík (North Iceland), this growing marine tourism industry has come under scrutiny for its impacts on the diverse species that reside in Skjálfandi Bay, including research on the negative impacts of noise pollution in the Bay. Using acoustic data and AIS positional data collected for the month of July in 2022, this study seeks to explore the overall noise contributions from two types of passenger vessels connected to the tourism industry; small-scale whale watching vessels and large-scale cruise ships and compare sound levels between these different vessel classes. Calculating the mean sound pressure levels (SPLrms) and sound exposure levels (SEL) for each vessel across all their trips within the Bay, with particular focus on 4 frequency bandwidths (63, 125, 250 & 500Hz) which have been frequently used as indicators of vessel noise. SPLs ranged from 137.00 to 154.50 dB re1μPa2 across the 4 target frequencies, with the highest SPL reading for small scale vessels (146.20 dB re1μPa2) falling within the 500 Hz frequency bandwidth, while the highest reading from the large-scale vessels (154.50 dB re1μPa2) fell within the 500 Hz frequency bandwidth. Exploring the sound levels of vessels, especially those belonging to an expanding industry that frequently encounters acoustically sensitive species is important and can inform management practices, aiding development of evidence base regulations and guidelines to mitigate marine noise pollution. Sjávar hávaðamengun er þekkt fyrir að hafa eyðileggjandi áhrif á tegundir og vistkerfi sjávar, og ein helsta uppsprettan er skipaumferð, sem versnar með hraðri aukningu sinni á ...